Two new genera of metalmark butterflies of North and Central America (Lepidoptera, Riodinidae) - Trujano-Ortega, Marysol (Zookeys, 2018)
Abstract. Two new genera of Riodinidae (Insecta: Lepidoptera) are described, Neoapodemia Trujano-Ortega, gen. n. (Neoapodemia nais (W. H. Edwards, 1876), comb. n., N. chisosensis Freeman, 1964, comb. n.) and Plesioarida Trujano-Ortega & García-Vázquez, gen. n. (Plesioarida palmerii palmerii (W. H. Edwards, 1870), comb. n., P. palmerii arizona (Austin, [1989]), comb. n., P. palmerii australis (Austin, [1989]), comb. n., P. hepburni hepburni (Godman & Salvin, 1886), comb. n., P. hepburni remota (Austin, 1991), comb. n., P. murphyi (Austin, [1989]), comb. n., P. hypoglauca hypoglauca (Godman & Salvin, 1878), comb. n., P. hypoglauca wellingi (Ferris, 1985), comb. n., P. walkeri (Godman & Salvin, 1886), comb. n., P. selvatica (De la Maza & De la Maza, 2017), comb. n.). Neoapodemia Trujano-Ortega, gen. n. is distributed in the southwestern USA and northeastern Mexico, while Plesioarida Trujano-Ortega & García-Vázquez, gen. n. is present from the southern USA to Central America. Species of these genera were previously classified as Apodemia C. Felder & R. Felder but molecular and morphological evidence separate them as new taxa. Morphological diagnoses and descriptions are provided for both new genera, including the main distinctive characters from labial palpi, prothoracic legs, wing venation and genitalia, as well as life history traits. A molecular phylogeny of one mitochondrial gene (COI) and two nuclear genes (EF-1a and wg) are also presented of most species of Apodemia, Neoapodemia Trujano-Ortega, gen. n., Plesioarida Trujano-Ortega & García-Vázquez, gen. n., and sequences of specimens from all tribes of Riodinidae. We compare the characters of Apodemia, Neoapodemia Trujano-Ortega, gen. n. and Plesioarida Trujano-Ortega & García-Vázquez, gen. n. and discuss the differences that support the description of these new taxa. This is a contribution to the taxonomy of the Riodinidae of North America of which the generic diversity is greater than previously recognized.